Determining the Best Route for Multiple Orders Clients in Food Delivery Services with Simulated Annealing Algorithm - Delila Amynadia Delila (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Food delivery services have been widely implemented by several companies such as Gojek Indonesia, Grab, Shopee Food and many more. Busyness and busy activity motivates someone to order online food delivery to meet their needs. For example, a worker who is tired of working all day orders food online for the dinner menu instead of cooking. Simulated annealing (SA) is an algorithm for performing general optimization. In this study, researchers built a system that determines the best delivery routes to deliver messages between customer meals using a simulated annealing algorithm. From the results of the study it was found that the application of the simulated annealing algorithm in finding the best route for multiple client food delivery in Binjai using data collected from drivers was quite good. Based on the results of trials conducted, Route [0-1-5-2-3-4] with a length of 6.29 km is the best route among others.